Impact of traumatic dental injuries on oral health-related quality of life of preschool children: A systematic review and meta-analysis - Borges, Tássia Silvana (PLoS One, 2017)
BACKGROUND: Observational studies have suggested that traumatic dental injuries (TDI) can lead to pain, loss of function and esthetic problems, with physical, emotional and social consequences for children and their families. However, population-based studies that investigate the impact of TDI on oral health-related quality of life (OHRQoL) among preschool children are scarce and offer conflicting results. The aim of the systematic review and meta-analysis was to evaluate the impact of TDI on OHRQoL among preschool children (PROSPERO-CRD42015032513). METHODS: An electronic search of six databases was performed in PubMed (MEDLINE), ISI Web of Science, Scopus, Science Direct, EMBASE and Google Scholar, with no language or publication date restrictions. The eligibility criteria were TDI as the exposure variable, OHRQoL as the outcome and a population of children up to six years of age. RevMan software was used for data analysis. Results are expressed as odds ratios with 95% confidence intervals for the total score of the Early Childhood Oral Health Impact Scale (ECOHIS) as well as the scores of the Child Impact Section (CIS) and Family Impact Section (FIS). The random effect model was chosen and heterogeneity was evaluated using the I(2) test. RESULTS: 2,013 articles were initially retrieved; 1,993 articles were excluded based on title and abstracts; 10 articles excluded after full-text analysis. Ten studies comprising a population of 7,461 preschool children were included in the systematic review and nine studies were included in the meta-analysis. TDI caused a negative impact on OHRQoL based on the overall ECOHIS (OR: 1.24; 95% CI: 1.08–1.43) and CIS (OR: 1.23; 95% CI: 1.07–1.41), but not the FIS (OR: 1.09; 95% CI: 0.90–1.32). CONCLUSIONS: TDI negatively impacted on OHRQoL of preschool children. The present findings indicate the need for TDI prevention and treatment programs in early childhood.